Composite current collector, preparation method and negative electrode-free sodium metal battery thereof

CN122950490APending Publication Date: 2026-10-20EAST GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611004496.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]鉴于上述问题,本发明的目的在于提供一种复合集流体、制备方法及其无负极钠金属电池,该复合集流体可有效解决现有技术中无负极钠电池钠金属沉积不均匀、界面稳定性差导致首效偏低和循环衰减快的技术问题

Benefits of technology

[0005]鉴于上述问题,本发明的目的在于提供一种复合集流体、制备方法及其无负极钠金属电池,该复合集流体可有效解决现有技术中无负极钠电池钠金属沉积不均匀、界面稳定性差导致首效偏低和循环衰减快的技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a composite current collector, its preparation method, and a negative electrode-free sodium metal battery. The composite current collector of this invention includes: a metal foil; a first coating disposed on the surface of the metal foil, the first coating comprising an adhesive and modified conductive carbon black, wherein the modified conductive carbon black is an inorganic element-doped porous conductive carbon black, and sodium-loving metal quantum dot particles are distributed within the pores of the modified conductive carbon black; and a second coating disposed on the side of the first coating away from the metal foil, the second coating being a fast ion conductor layer. This invention, by sequentially constructing a first coating containing modified conductive carbon black and sodium-loving metal quantum dot particles, and a second coating containing a fast ion conductor film on the surface of the metal foil, effectively reduces the overpotential of sodium metal nucleation, induces uniform deposition, inhibits dendrite growth, alleviates volume expansion, and constructs a stable interface through the synergistic effect between the coatings, thereby effectively improving the initial efficiency and cycle performance of the negative electrode-free sodium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium metal battery technology, and in particular to a composite current collector, its preparation method, and a sodium metal battery without a negative electrode. Background Technology

[0002] Sodium-ion batteries benefit from the widespread availability and low cost of sodium resources, making them a promising alternative to lithium-ion batteries. However, current sodium-ion batteries typically use hard carbon as the anode material, resulting in relatively low energy density and high cost, which limits their large-scale commercial application. To address this, researchers are attempting to develop anode-free sodium batteries, eliminating the traditional anode material and directly depositing and stripping sodium metal onto the current collector surface, thereby achieving higher energy density and lower manufacturing costs.

[0003] In a negative electrode-less sodium battery, sodium metal undergoes reversible deposition and stripping on the surface of the negative electrode current collector during charging and discharging. However, when sodium metal is deposited directly on the current collector surface, due to the uneven distribution of the surface electric field and the lack of nucleation sites, sodium metal tends to grow irregularly, forming dendritic or moss-like deposits. This irregular deposition morphology not only reduces the coulombic efficiency of sodium deposition / stripping but also easily punctures the separator, causing a short circuit. Simultaneously, the solid electrolyte interface film formed in situ at the interface between the electrolyte and sodium metal usually lacks mechanical strength and has uneven composition, making it prone to rupture during repeated volume expansion and contraction, continuously consuming active sodium, resulting in low initial efficiency and rapid degradation of cycle life.

[0004] Therefore, how to design a composite current collector that can induce uniform sodium metal deposition, suppress dendrite growth, and construct a stable interface to improve the first-efficiency and cycle performance of anode-free sodium batteries is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] In view of the above problems, the purpose of this invention is to provide a composite current collector, a preparation method thereof, and a sodium metal battery without a negative electrode. This composite current collector can effectively solve the technical problems of uneven sodium metal deposition and poor interface stability leading to low initial efficiency and rapid cycle decay in the prior art sodium metal batteries without a negative electrode.

[0006] To achieve the above objectives, a first aspect of the present invention provides a composite current collector, comprising: Metal foil; The first coating is applied to the surface of the metal foil. The first coating includes an adhesive and modified conductive carbon black. The modified conductive carbon black is an inorganic element-doped porous conductive carbon black. Sodium-loving metal quantum dot particles are distributed in the pores of the modified conductive carbon black. The second coating is disposed on the surface of the first coating away from the metal foil, and the second coating is a fast ion conductor layer.

[0007] Compared with existing technologies, in the composite current collector of this invention, the first coating includes modified conductive carbon black and sodium-loving metal quantum dot particles distributed within the pores of the modified conductive carbon black. The porous structure of the modified conductive carbon black provides a large specific surface area and abundant pores, which can absorb and buffer the volume stress generated by sodium metal during deposition and stripping. On the other hand, the defect sites formed by its inorganic element doping can regulate the local electric field distribution, providing uniform adsorption and nucleation sites for sodium ions and guiding the subsequent orderly deposition of sodium metal. The sodium-loving metal quantum dot particles distributed within the pores of the modified conductive carbon black easily form an alloy phase with metallic sodium, significantly reducing the nucleation overpotential of sodium and thermodynamically reducing the randomness of initial deposition, inducing sodium to nucleate uniformly with smaller nucleation size and higher nucleation density. The fast ion conductor layer on the surface of the first coating has high ionic conductivity and low electronic conductivity, enabling spatial decoupling of electrons and ions. That is, electrons are transported in the underlying conductive carbon black network, while sodium ions migrate directionally to the deposition sites through the surface ion conductor film layer, thereby avoiding local charge accumulation and further suppressing dendrite growth. Furthermore, this fast-ion conductor layer can also serve as an artificial SEI film, possessing excellent mechanical strength and chemical inertness. Working synergistically with the bottom conductive layer, it guides the formation of a stable SEI film rich in inorganic substances (such as NaF and Na₂CO₃), enhancing interfacial stability. Therefore, the composite current collector of this invention can effectively improve the initial efficiency and cycle performance of sodium metal batteries.

[0008] Furthermore, the mass ratio of the adhesive, modified conductive carbon black, and sodium-loving metal quantum dot particles is 1:6~8:1~3.

[0009] Furthermore, the thickness of the first coating is 1.5µm to 5µm.

[0010] Furthermore, the loading of the first coating is 0.3 mg / cm³. 2 ~0.8 mg / cm 2 If the loading is too low, the coating will not cover the entire surface and will not provide sufficient nucleation sites and volume buffering capacity; if the loading is too high, the coating will be too thick, increasing the ion diffusion path length and affecting the kinetic performance.

[0011] Furthermore, the thickness of the second coating is 10 nm to 30 nm. This thickness range provides a complete ion conduction path and electron blocking effect without excessively increasing the interface impedance.

[0012] Furthermore, the substrate material for the modified conductive carbon black includes at least one of acetylene black, Ketjen black, and Super P.

[0013] Furthermore, the sodium-loving metal quantum dot particles include at least one of gold quantum dot particles, silver quantum dot particles, indium quantum dot particles, zinc quantum dot particles, bismuth quantum dot particles, and tin quantum dot particles.

[0014] Furthermore, the inorganic element is selected from at least one of nitrogen, sulfur, fluorine, and phosphorus.

[0015] Furthermore, the material of the fast ion conductor layer is selected from at least one of sodium aluminum titanium phosphate, sodium titanium phosphate, sodium zirconium phosphate, sodium monofluorophosphate, and alumina.

[0016] Furthermore, the substrate material of the modified conductive carbon black is selected from Ketjen black; the sodium-loving metal quantum dot particles are selected from zinc quantum dot particles; and the material of the fast ion conductor layer is selected from sodium aluminum titanium phosphate. Among these, zinc quantum dot particles have a lower cost and a moderate alloying potential with sodium, effectively reducing the nucleation barrier; sodium aluminum titanium phosphate has high ionic conductivity and extremely low electronic conductivity, enabling efficient selective transport of sodium ions; and Ketjen black possesses excellent conductivity and high porosity. Using Ketjen black, zinc quantum dot particles, and sodium aluminum titanium phosphate as materials for forming the first and second coatings can further improve the low-temperature performance of the anode-free sodium metal battery, while effectively enhancing its initial coulombic efficiency and cycle performance. A second aspect of the present invention provides a method for preparing the aforementioned composite current collector, comprising the steps of: (1) The conductive carbon black is first acid-treated and then inorganic element doping is performed to obtain modified conductive carbon black; (2) The sodium-loving metal source, surfactant and modified conductive carbon black are mixed and reacted in a solvent composed of water, ethanol and ammonia to form hydroxide on the surface of the modified conductive carbon black. The hydroxide is then decomposed by heat treatment in a reducing atmosphere to generate sodium-loving metal quantum dot particles, thus obtaining modified conductive carbon black with sodium-loving metal quantum dot particles attached. (3) The modified conductive carbon black with sodium-loving metal quantum dot particles attached is mixed with a binder to form a slurry, which is then coated onto the surface of a metal foil to form a first coating. (4) A fast ion conductor layer is deposited on the surface of the first coating by atomic layer deposition technology, and a second coating is formed after heat treatment to obtain a composite current collector.

[0017] In the preparation method of this invention, acid treatment completes the surface modification, pore formation and impurity removal of carbon materials in one step, inorganic element doping introduces active sites, in-situ deposition and reduction processes achieve uniform loading of metal quantum dot particles on the surface of carbon materials, and atomic layer deposition can precisely control the thickness and uniformity of fast ion conductor thin film layers.

[0018] Further, in step (1), the acid treatment is carried out in a nitric acid solution with a concentration of 14 mol / L to 15 mol / L, a water-to-nitric acid volume ratio of 15 to 5:1, a treatment temperature of 60℃ to 80℃, and a treatment time of 6h to 12h. These acid treatment conditions can effectively form oxygen-containing functional groups and generate micro-nano pores on the surface of carbon materials, while effectively removing impurities contained in conductive carbon black.

[0019] Furthermore, in step (1), inorganic element doping is achieved through gas phase doping.

[0020] Further, in step (2), the mass ratio of surfactant to modified porous conductive carbon black is 0.05~0.1:1, the volume ratio of water, ethanol and ammonia is 8:1~3:0.5~2, the concentration of the sodium-loving metal source in the reaction solution is 0.1mol / L~2mol / L, the reducing atmosphere is a mixture of argon and hydrogen, the volume ratio of argon to hydrogen is 10:1~2, the reduction heat treatment temperature is 300℃~500℃, and the holding time is 1h~3h. Under these conditions, the sodium-loving metal source uniformly forms hydroxide on the surface of conductive carbon black in an alkaline environment, and then is reduced by hydrogen to transform into nanoscale metal quantum dot particles. The size of the quantum dots is controllable and the distribution is uniform.

[0021] Furthermore, in step (4), the reaction chamber temperature of the atomic layer deposition process is 150℃~200℃, the working pressure is 0.2Torr~0.5Torr, and the number of cycles is 10~20.

[0022] Furthermore, in step (4), the heat treatment includes treatment at 500°C to 600°C for 1 to 3 hours under a protective atmosphere. Heat treatment helps to improve the crystallinity of the fast ion conductor thin film layer, enhancing its ionic conductivity and structural stability.

[0023] A third aspect of the present invention provides a negative electrode-free sodium metal battery, comprising the aforementioned composite current collector or the composite current collector prepared by the aforementioned method of preparing the composite current collector. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the composite current collector of the present invention; Figure 2 This is a diagram showing the sodium deposition effect after the first charge cycle in Embodiment 1 of the present invention. Detailed Implementation

[0025] The composite current collector provided by this invention, such as Figure 1As shown, it includes: a metal foil; a first coating disposed on the surface of the metal foil, the first coating including an adhesive and modified conductive carbon black, the modified conductive carbon black being inorganic element-doped porous conductive carbon black, the channels of the modified conductive carbon black containing sodium-loving metal quantum dot particles; and a second coating disposed on the side of the first coating away from the metal foil, the second coating being a fast ion conductor layer.

[0026] The metal foil can be selected from any one of aluminum foil, copper foil, porous aluminum foil, porous copper foil, and alloyed foil. Preferably, the metal foil is selected from aluminum foil. The thickness of the metal foil can be 5μm to 20μm. For example, the thickness of the metal foil can be, but is not limited to, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 14μm, 15μm, 16μm, 18μm, and 20μm.

[0027] The thickness of the first coating is 1.5µm to 5µm. For example, the thickness of the first coating can be, but is not limited to, 1.5µm, 2µm, 2.5µm, 3µm, 3.5µm, 4µm, 4.5µm, or 5µm. The loading of the first coating is 0.3 mg / cm³. 2 ~0.8mg / cm 2 As an example, the loading of the first coating may, but is not limited to, 0.3 mg / cm³. 2 0.4 mg / cm 2 0.5 mg / cm 2 0.6 mg / cm 2 0.7 mg / cm 2 0.8 mg / cm 2 .

[0028] The substrate material of the modified conductive carbon black includes at least one selected from acetylene black, Ketjen black, and Super P. Preferably, the substrate material of the modified conductive carbon black is selected from Ketjen black. The specific surface area of ​​the modified conductive carbon black can be 200 m². 2 / g~1500m 2 / g, as an example, the specific surface area of ​​the modified conductive carbon black can be, but is not limited to, 200 m² / g. 2 / g、300m 2 / g、400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g, 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g, 1400m 2 / g, 1500m 2 / g. The particle size Dv50 of the modified conductive carbon black can be 20nm~100nm. For example, the particle size Dv50 of the modified conductive carbon black can be, but is not limited to, 20nm, 40nm, 50nm, 60nm, 80nm, or 100nm.

[0029] The sodium-loving metal quantum dot particles include at least one of gold quantum dot particles, silver quantum dot particles, indium quantum dot particles, zinc quantum dot particles, bismuth quantum dot particles, and tin quantum dot particles. Preferably, the sodium-loving metal quantum dot particles are selected from zinc quantum dot particles. Further, zinc quantum dot particles can use zinc acetate dihydrate as the metal source, gold quantum dot particles can use chloroauric acid as the metal source, and silver quantum dot particles can use silver nitrate as the metal source. It is important to note that the sodium-loving metal quantum dot particles of the present invention specifically refer to sodium-loving metal particles with a particle size Dv50 of 4-10 nm. Sodium-loving metals refer to metals that can form alloys or intermetallic compounds with metallic sodium and can act as sodium nucleation sites and reduce sodium nucleation overpotential during sodium deposition, including but not limited to one or more of In, Sn, Zn, Bi, Sb, Pb, Au, Ag, Mg, and Al.

[0030] The inorganic element is selected from at least one of nitrogen, sulfur, fluorine, and phosphorus. The content of the inorganic element in the modified conductive carbon black is 0.5% to 5%. As an example, the content of the inorganic element in the modified conductive carbon black may be, but is not limited to, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.

[0031] The adhesive can be selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, and styrene-butadiene rubber.

[0032] The mass ratio of the binder, modified conductive carbon black, and sodium-loving metal quantum dot particles is 1:6 to 8:1 to 3. Preferably, the mass ratio of the binder, modified conductive carbon black, and sodium-loving metal quantum dot particles is 1:6 to 8:1 to 2. As an example, the mass ratio of the binder, modified conductive carbon black, and sodium-loving metal quantum dot particles may be, but is not limited to, 1:6:1, 1:7:1, 1:8:1, 1:6:2, 1:7:2, 1:8:2, 1:6:3, 1:7:3, or 1:8:3.

[0033] The thickness of the second coating is 10nm to 30nm. As an example, the thickness of the second coating may be, but is not limited to, 10nm, 12nm, 14nm, 15nm, 16nm, 18nm, 20nm, 22nm, 24nm, 25nm, 26nm, 28nm, or 30nm.

[0034] The fast ion conductor layer is selected from at least one of sodium aluminum titanium phosphate, sodium titanium phosphate, sodium zirconium phosphate, sodium monofluorophosphate, and alumina. Preferably, the fast ion conductor layer is selected from sodium aluminum titanium phosphate. Sodium aluminum titanium phosphate can be prepared by atomic layer deposition using sodium methoxide as the sodium source, tetraisopropyl titanate as the titanium source, trimethylaluminum as the aluminum source, trimethyl phosphate as the phosphorus source, and ozone as the oxygen source.

[0035] The preparation method of the aforementioned composite current collector provided by the present invention includes the following steps: (1) Acid treatment is performed on conductive carbon black, followed by inorganic element doping treatment to obtain modified conductive carbon black; (2) Sodium-loving metal source, surfactant and modified conductive carbon black are mixed and reacted in a solvent composed of water, ethanol and ammonia to form hydroxide on the surface of modified conductive carbon black from sodium-loving metal source, and then heat treatment is performed in a reducing atmosphere to decompose the hydroxide to generate sodium-loving metal quantum dot particles to obtain modified conductive carbon black with sodium-loving metal quantum dot particles attached; (3) Modified conductive carbon black with sodium-loving metal quantum dot particles attached is mixed with binder to form a slurry, and coated on the surface of metal foil to form a first coating; (4) Fast ion conductor layer is deposited on the surface of the first coating by atomic layer deposition technology, and a second coating is formed after heat treatment to obtain composite current collector.

[0036] In step (1), the acid treatment is carried out in a nitric acid solution with a concentration of 14 mol / L to 15 mol / L and a volume ratio of water to concentrated nitric acid of 15 to 5:1. For example, the concentration of nitric acid can be, but is not limited to, 14 mol / L, 14.2 mol / L, 14.4 mol / L, 14.5 mol / L, 14.6 mol / L, 14.8 mol / L, or 15 mol / L; the volume ratio of water to concentrated nitric acid can be 15:1, 14:1, 13:1, 12:1, 11:1, 10:1, 9:1, 8:1, 7:1, 6:1, or 5:1, but is not limited thereto. Other values ​​not listed within the numerical range of this invention are also applicable.

[0037] The acid treatment temperature is 60℃~80℃. For example, the acid treatment temperature is 60℃, 65℃, 70℃, 75℃, or 80℃, but is not limited to these values. Other values ​​not listed within the numerical range of this invention are also applicable. The acid treatment time is 6h~12h. For example, the acid treatment time can be, but is not limited to, 6h, 8h, 10h, or 12h, but is not limited to these values. Other values ​​not listed within the numerical range of this invention are also applicable.

[0038] Inorganic element doping is achieved through gas-phase doping. Specifically, if the inorganic doping element is nitrogen, the acid-treated conductive carbon black is treated in a nitrogen atmosphere at 500℃~700℃ for 4~8 hours. As an example, the nitrogen doping temperature can be, but is not limited to, 500℃, 550℃, 600℃, 650℃, or 700℃; the holding time can be, but is not limited to, 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours. If the inorganic doping element is fluorine, the acid-treated conductive carbon black is treated in a fluorine atmosphere diluted with an inert gas at 100℃~300℃ for 4 hours~10 hours. As an example, the fluorine doping temperature can be, but is not limited to, 100℃, 150℃, 200℃, 250℃, or 300℃; the holding time can be, but is not limited to, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. If the inorganic doping element is phosphorus, then red phosphorus powder is used as the phosphorus source, and the acid-treated conductive carbon black is kept at 500℃~700℃ for 4h~10h. As an example, the phosphorus doping treatment temperature can be, but is not limited to, 500℃, 550℃, 600℃, 650℃, or 700℃; the holding time can be, but is not limited to, 4h, 5h, 6h, 7h, 8h, 9h, or 10h. The inorganic doping element is sulfur, with carbon disulfide as the sulfur source. The acid-treated conductive carbon black is kept at 500℃~1000℃ for 2h~8h. As an example, the temperature of sulfur doping treatment can be, but is not limited to, 500, 550, 600, 650, 700, 750, 800℃, 850℃, 900℃, 950℃, or 1000℃; the holding time can be, but is not limited to, 2h, 3h, 4h, 5h, 6h, 7h, or 8h.

[0039] In step (2), the mass ratio of surfactant to modified porous conductive carbon black is 0.05 to 0.1:1. For example, the mass ratio of surfactant to modified porous conductive carbon black may be, but is not limited to, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, or 0.1:1. The concentration of sodium-loving metal source in the reaction solution is 0.1 mol / L to 2 mol / L. For example, the concentration of sodium-loving metal source in the reaction solution may be, but is not limited to, 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, or 2 mol / L.

[0040] The sodium-loving metal source can be a sodium-loving metal salt, specifically at least one of zinc acetate, chloroauric acid, silver nitrate, indium chloride, bismuth nitrate, and tin acetate, but the invention is not limited thereto. The surfactant can be at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyvinylpyrrolidone, polyethylene glycol, oleic acid, oleylamine, and alkyl thiols, but the invention is not limited thereto.

[0041] The volume ratio of water, ethanol and ammonia is 8:1 to 3:0.5 to 2. As an example, the volume ratio of water, ethanol and ammonia may be, but is not limited to, 8:1:0.5, 8:1:1, 8:1:1.5, 8:1:2, 8:2:0.5, 8:2:1, 8:2:1.5, 8:2:2, 8:3:0.5, 8:3:1, 8:3:1.5, and 8:3:2.

[0042] The reducing atmosphere is a mixture of argon and hydrogen, with a volume ratio of argon to hydrogen of 10:1 to 2. For example, the volume ratio of argon to hydrogen may be, but is not limited to, 10:1, 10:1.5, or 10:2.

[0043] The reduction heat treatment temperature is 300℃~500℃. For example, the reduction heat treatment temperature may be, but is not limited to, 300℃, 350℃, 400℃, 450℃, or 500℃. The reduction heat treatment holding time is 1h~3h. For example, the reduction heat treatment holding time may be, but is not limited to, 1h, 1.5h, 2h, 2.5h, or 3h.

[0044] In step (3), forming the first coating specifically involves adding modified conductive carbon black with attached sodium-loving metal quantum dot particles and a binder to an N-methylpyrrolidone solvent and stirring for 12-18 hours to form a uniform slurry. The solid content of the slurry is 5%-30%, and the viscosity range is 1000 mP.s-6500 mP.s. The slurry is then coated onto the surface of an aluminum foil and vacuum-dried at 60°C for 12 hours to obtain the first coating. As an example, the stirring time may be, but is not limited to, 12h, 13h, 14h, 15h, 16h, 17h, or 18h; the solid content of the slurry may be, but is not limited to, 5%, 10%, 15%, 20%, 25%, or 30%; and the viscosity of the slurry may be, but is not limited to, 1000 mP.s, 1500 mP.s, 2000 mP.s, 2500 mP.s, 3000 mP.s, 3500 mP.s, 4000 mP.s, 4500 mP.s, 5000 mP.s, 5500 mP.s, 6000 mP.s, or 6500 mP.s.

[0045] In step (4), the reaction chamber temperature of the atomic layer deposition process is 150°C to 200°C, the working pressure is 0.2 Torr to 0.5 Torr, and the number of cycles is 10 to 20. As an example, the reaction chamber temperature of the atomic layer deposition process can be, but is not limited to, 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C; the working pressure can be, but is not limited to, 0.2 Torr, 0.3 Torr, 0.4 Torr, or 0.5 Torr; and the number of cycles can be, but is not limited to, 10, 12, 15, 18, or 20.

[0046] Heat treatment includes treatment at 500°C to 600°C for 1 to 3 hours under a protective atmosphere. For example, the temperature of heat treatment may be, but is not limited to, 500°C, 520°C, 550°C, 580°C, or 600°C; and the time of heat treatment may be, but is not limited to, 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.

[0047] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting it.

[0048] Example 1 This embodiment provides a composite current collector and its preparation method, including the following steps: (1) Weigh 8g of Ketjen black conductive carbon and place it in a beaker. Add 120mL of deionized water to disperse it and stir for 1h. Then add 12mL of nitric acid with a concentration of 14.5mol / L. Heat in a fume hood at 70℃ for 8h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve and bag. Place the acid-treated Ketjen black conductive carbon in a tube furnace and purge with nitrogen. First, purge for 1h to remove the oxygen adsorbed in the tube furnace and the material. Then, heat the tube furnace to 600℃ at a heating rate of 2℃ / min and hold for 6h. After the tube furnace cools down, take out the powder and bag it to obtain modified conductive carbon black. The N content was found to be 3.0% by elemental analysis.

[0049] (2) Weigh 5g of the modified conductive carbon black and place it in a blue-capped bottle. Add 80mL of deionized water, 20mL of ethanol, and 10mL of ammonia water for dispersion. Then weigh 0.3g of hexadecyltrimethylammonium bromide and stir for 1.5h. Then weigh an appropriate amount of zinc acetate dihydrate and add it to the solution to dissolve it, so that the concentration of zinc acetate in the reaction solution is 0.5mol / L. Place the blue-capped bottle in an oven and react at 90℃ for 4h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve, and bag. The obtained powder was placed in an atmosphere tube furnace, and argon gas was introduced. The furnace was first purged for 1 hour to remove the oxygen adsorbed by the material and the tube furnace. Then, a mixture of argon and hydrogen gas (volume ratio 10:1.5) was introduced. The tube furnace was heated to 400°C at a heating rate of 2°C / min and held at that temperature for 2 hours. After the tube furnace cooled down, the powder was removed, sieved, and bagged to obtain modified conductive carbon black loaded with zinc quantum dot particles.

[0050] (3) Weigh 0.9 g of the modified conductive carbon black loaded with zinc quantum dot particles (containing 0.15 g of zinc quantum dot particles) and 0.1 g of polyvinylidene fluoride, add them to N-methylpyrrolidone solvent, and stir for 15 h to form a uniform slurry (solid content 8.3%, viscosity about 4600 mPa·s). Then coat the slurry onto the surface of aluminum foil (thickness 12 μm) and vacuum dry at 60 °C for 12 h to form the first coating. The thickness of the first coating on the aluminum foil substrate is 2 µm, and the loading is 0.5 mg / cm. 2 .

[0051] (4) The aluminum foil with the first coating was cut into circular pieces and placed in the ALD reaction chamber. Sodium methoxide was used as the sodium source, trimethylaluminum as the aluminum source, tetraisopropyl titanate as the titanium source, trimethyl phosphate as the phosphorus source, and ozone as the oxygen source. The temperature of the reaction chamber was set to 175℃. High-purity nitrogen was first introduced as the carrier gas and purge gas, with a flow rate of 30 sccm and a working pressure of 0.3 Torr. The sodium source, titanium source, aluminum source, phosphorus source, and oxygen source were pulsed in sequence, with purge times of 2s, 1.5s, 0.3s, 2s, and 20s, respectively. After each purge, high-purity nitrogen was used for 20s purging. This cycle was repeated 15 times, and the deposition thickness was 20nm, resulting in a sodium aluminum titanium phosphate fast ion conductor layer. The deposited electrode was transferred to a tube furnace, with argon as the protective atmosphere. The heating rate was 5℃ / min, and the temperature was raised to 550℃. The reaction was carried out for 2h to form the second coating. After cooling, the composite current collector was obtained.

[0052] Example 2 The difference between this embodiment and Embodiment 1 is that: (2) Weigh 5g of modified conductive carbon black and place it in a blue-capped bottle. Add 80mL of deionized water, 20mL of ethanol, and 10mL of ammonia water for dispersion. Then weigh 0.3g of hexadecyltrimethylammonium bromide and stir for 1.5h. Then weigh an appropriate amount of tin acetate and dissolve it in the solution to make the concentration of tin acetate in the reaction solution 0.5mol / L. Place the blue-capped bottle in an oven and react at 90℃ for 4h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve, and bag. The obtained powder was placed in an atmosphere tube furnace, and argon gas was introduced. First, the furnace was ventilated for 1 hour to remove oxygen adsorbed by the material. Then, a mixture of argon and hydrogen (volume ratio 10:1.5) was introduced, and the furnace was heated to 400°C at a rate of 2°C / min and held at that temperature for 2 hours. After the furnace cooled, the powder was removed, sieved, and bagged to obtain modified conductive carbon black loaded with tin quantum dot particles. The remaining steps (1), (3) and (4) are the same as in Example 1.

[0053] Example 3 The difference between this embodiment and Embodiment 1 is that: (1) Weigh 8g of acetylene black conductive carbon and place it in a beaker. Add 120mL of deionized water to disperse it and stir for 1h. Then add 12mL of nitric acid with a concentration of 14.5mol / L. Heat in a fume hood at 70℃ for 8h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve and bag. Place the acid-treated acetylene black conductive carbon in a tube furnace and purge with nitrogen. First, purge for 1h to remove the oxygen adsorbed in the tube furnace and the material. Then, heat the tube furnace to 600℃ at a heating rate of 2℃ / min and hold for 6h. After the tube furnace cools down, take out the powder and bag it to obtain modified conductive carbon black with a nitrogen content of 1.5%.

[0054] (4) The aluminum foil with the first coating was cut into circular pieces and placed in the ALD reaction chamber. Trimethylaluminum was used as the aluminum source and ozone as the oxygen source. The temperature of the reaction chamber was set to 175℃. High-purity nitrogen was first introduced as the carrier gas and purge gas, with a flow rate of 30 sccm and a working pressure of 0.3 Torr. The aluminum source and oxygen source were pulsed sequentially, with purge times of 0.3s and 20s, respectively. After each purge, high-purity nitrogen was used for 20s purging. This cycle was repeated 15 times, and the deposition thickness was 20nm, resulting in an alumina fast ion conductor layer. The deposited electrode was transferred to a tube furnace, with argon as the protective atmosphere. The heating rate was 5℃ / min, and the temperature was raised to 550℃. The reaction was carried out for 2 hours to form the second coating. After cooling, the composite current collector was obtained.

[0055] The remaining steps (2) and (3) are the same as in Example 1.

[0056] Example 4 The difference between this embodiment and Embodiment 1 is that: (2) Weigh 5g of the modified conductive carbon black and place it in a blue-capped bottle. Add 80mL of deionized water, 20mL of ethanol, and 10mL of ammonia water for dispersion. Then weigh 0.3g of hexadecyltrimethylammonium bromide and stir for 1.5h. Then weigh an appropriate amount of zinc acetate dihydrate and add it to the solution to dissolve it, so that the concentration of zinc acetate in the reaction solution is 1.2mol / L. Place the blue-capped bottle in an oven and react at 90℃ for 4h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve, and bag. The obtained powder was placed in an atmosphere tube furnace, and argon gas was introduced. The furnace was first purged for 1 hour to remove the oxygen adsorbed by the material and the tube furnace. Then, a mixture of argon and hydrogen gas (volume ratio 10:1.5) was introduced. The tube furnace was heated to 400°C at a heating rate of 2°C / min and held at that temperature for 2 hours. After the tube furnace cooled down, the powder was removed, sieved, and bagged to obtain modified conductive carbon black loaded with zinc quantum dot particles.

[0057] (3) Weigh 0.9 g of the modified conductive carbon black loaded with zinc quantum dot particles (containing 0.25 g of zinc quantum dot particles) and 0.1 g of polyvinylidene fluoride, add them to N-methylpyrrolidone solvent, and stir for 15 h to form a uniform slurry (solid content 8.3%, viscosity about 4780 mPa·s). Then coat the slurry onto the surface of aluminum foil (thickness 12 μm) and vacuum dry at 60 °C for 12 h to form the first coating. The thickness of the first coating on the aluminum foil substrate is 2 µm, and the loading is 0.5 mg / cm. 2 .

[0058] The remaining steps (1) and (4) are the same as in Example 1.

[0059] Example 5 The difference between this embodiment and Embodiment 1 is that: (1) Weigh 8g of Ketjen Black conductive carbon and place it in a beaker. Add 120mL of deionized water to disperse it and stir for 1h. Then add 12mL of 14.5mol / L nitric acid. Heat in a fume hood at 70℃ for 8h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve and bag. Acid-treated Ketjen black conductive carbon black and carbon disulfide were placed in a tube furnace. The carbon disulfide was placed in a ceramic boat with a loading of 10 mL, located near the gas inlet. The conductive carbon black was placed in another ceramic boat, located near the gas outlet. Argon gas (flow rate of 0.5 L / min) was introduced and purged for 1 hour to remove oxygen adsorbed in the tube furnace and by the materials. Then, the tube furnace was heated to 600 °C at a heating rate of 2 °C / min and held at that temperature for 6 hours. After the tube furnace cooled down, the powder was removed and bagged to obtain modified conductive carbon black. The sulfur content was found to be 2.5% by elemental analysis.

[0060] The remaining steps (2), (3), and (4) are the same as in Example 1.

[0061] Comparative Example 1 This comparative example provides a composite current collector and its preparation method, including the following steps: (1) Weigh 8g of Ketjen black conductive carbon and place it in a beaker. Add 120mL of deionized water to disperse it and stir for 1h. Then add 12mL of nitric acid with a concentration of 14.5mol / L. Heat in a fume hood at 70℃ for 8h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve and bag. Place the acid-treated Ketjen black conductive carbon in a tube furnace and purge with nitrogen. First, purge for 1h to remove the oxygen adsorbed in the tube furnace and the material. Then, heat the tube furnace to 600℃ at a heating rate of 2℃ / min and hold for 6h. After the tube furnace cools down, take out the powder and bag it to obtain modified conductive carbon black with a nitrogen content of 3.0%.

[0062] (2) Weigh 0.9 g of the modified conductive carbon black and 0.1 g of polyvinylidene fluoride, add them to N-methylpyrrolidone solvent, and stir for 15 h to form a uniform slurry (solid content 8.3%, viscosity about 4750 mPa·s). Then coat the slurry onto the surface of aluminum foil (thickness 12 μm) and vacuum dry at 60 °C for 12 h to form the first coating. The thickness of the first coating on the aluminum foil substrate is 2 µm, and the loading is 0.5 mg / cm. 2 .

[0063] (3) The aluminum foil with the first coating was cut into circular pieces and placed in the ALD reaction chamber. Sodium methoxide was used as the sodium source, trimethylaluminum as the aluminum source, tetraisopropyl titanate as the titanium source, trimethyl phosphate as the phosphorus source, and ozone as the oxygen source. The temperature of the reaction chamber was set to 175℃. High-purity nitrogen was first introduced as the carrier gas and purge gas, with a flow rate of 30 sccm and a working pressure of 0.3 Torr. The sodium source, titanium source, aluminum source, phosphorus source, and oxygen source were pulsed in sequence, with purge times of 2s, 1.5s, 0.3s, 2s, and 20s, respectively. After each purge, high-purity nitrogen was used for a 20s purge. This cycle was repeated 15 times, and the deposition thickness was 20 nm to obtain a sodium aluminum titanium phosphate fast ion conductor layer. The deposited electrode was transferred to a tube furnace, and argon was used as the protective atmosphere. The heating rate was 5℃ / min, and the temperature was raised to 550℃. The reaction was carried out for 2 hours to form the second coating. After cooling, the composite current collector was obtained.

[0064] Comparative Example 2 This comparative example provides a composite current collector and its preparation method, including the following steps: (1) Weigh 8g of Ketjen black conductive carbon and place it in a beaker. Add 120mL of deionized water to disperse it and stir for 1h. Then add 12mL of nitric acid with a concentration of 14.5mol / L. Heat in a fume hood at 70℃ for 8h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve and bag. Place the acid-treated Ketjen black conductive carbon in a tube furnace and purge with nitrogen. First, purge for 1h to remove the oxygen adsorbed in the tube furnace and the material. Then, heat the tube furnace to 600℃ at a heating rate of 2℃ / min and hold for 6h. After the tube furnace cools down, take out the powder and bag it to obtain modified conductive carbon black with a nitrogen content of 3.0%.

[0065] (2) Weigh 5g of the modified conductive carbon black and place it in a blue-capped bottle. Add 80mL of deionized water, 20mL of ethanol, and 10mL of ammonia water for dispersion. Then weigh 0.3g of hexadecyltrimethylammonium bromide and stir for 1.5h. Then weigh an appropriate amount of zinc acetate dihydrate and add it to the solution to dissolve it, so that the concentration of zinc acetate in the reaction solution is 0.5mol / L. Place the blue-capped bottle in an oven and react at 90℃ for 4h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve, and bag. The obtained powder was placed in an atmosphere tube furnace, and argon gas was introduced. The furnace was first purged for 1 hour to remove the oxygen adsorbed by the material and the tube furnace. Then, a mixture of argon and hydrogen gas (volume ratio 10:1.5) was introduced. The tube furnace was heated to 400°C at a heating rate of 2°C / min and held at that temperature for 2 hours. After the tube furnace cooled down, the powder was removed, sieved, and bagged to obtain modified conductive carbon black loaded with zinc quantum dot particles.

[0066] (3) Weigh 0.9 g of the modified conductive carbon black loaded with zinc quantum dot particles (containing 0.15 g of zinc quantum dot particles) and 0.1 g of polyvinylidene fluoride, add them to N-methylpyrrolidone solvent, and stir for 15 h to form a uniform slurry (solid content 8.3%, viscosity about 4600 mPa·s). Then coat the slurry onto the surface of aluminum foil (thickness 12 μm) and vacuum dry at 60 °C for 12 h to form the first coating. The thickness of the first coating on the aluminum foil substrate is 2 µm; the loading is 0.5 mg / cm. 2 Thus, a composite current collector is obtained.

[0067] Comparative Example 3 This comparative example provides a composite current collector and its preparation method, including the following steps: (1) Weigh 5g of raw Ketjen Black conductive carbon (i.e., unmodified Ketjen Black conductive carbon) and place it in a blue-capped bottle. Add 80mL of deionized water, 20mL of ethanol, and 10mL of ammonia water for dispersion treatment. Then weigh 0.3g of hexadecyltrimethylammonium bromide and stir for 1.5h. Then weigh an appropriate amount of zinc acetate dihydrate and add it to the solution to dissolve it, so that the concentration of zinc acetate in the reaction solution is 0.5mol / L. Place the blue-capped bottle in an oven and react at 90℃ for 4h. After heating, filter and wash with ethanol and water 3 times each. Finally, place it in a vacuum oven and dry at 90℃ for 18h. After drying, crush, sieve, and bag. The obtained powder was placed in an atmosphere tube furnace, and argon gas was introduced. The furnace was first purged for 1 hour to remove the oxygen adsorbed by the material and the tube furnace. Then, a mixture of argon and hydrogen gas (volume ratio 10:1.5) was introduced. The tube furnace was heated to 400°C at a heating rate of 2°C / min and held at that temperature for 2 hours. After the tube furnace cooled down, the powder was removed, sieved, and bagged to obtain modified conductive carbon black loaded with zinc quantum dot particles.

[0068] (2) Weigh 0.9 g of the original Ketjen Black conductive carbon loaded with zinc quantum dot particles (containing 0.05 g of zinc quantum dot particles) and 0.1 g of polyvinylidene fluoride, add them to N-methylpyrrolidone solvent, and stir for 15 h to form a uniform slurry (solid content 8.3%, viscosity about 4550 mPa·s). Then coat the slurry onto the surface of aluminum foil (thickness 12 μm) and vacuum dry at 60 °C for 12 h to form the first coating. The thickness of the first coating on the aluminum foil substrate is 2 µm, and the loading is 0.5 mg / cm. 2 .

[0069] (3) The aluminum foil with the first coating was cut into circular pieces and placed in the ALD reaction chamber. Sodium methoxide was used as the sodium source, trimethylaluminum as the aluminum source, tetraisopropyl titanate as the titanium source, trimethyl phosphate as the phosphorus source, and ozone as the oxygen source. The temperature of the reaction chamber was set to 175℃. High-purity nitrogen was first introduced as the carrier gas and purge gas, with a flow rate of 30 sccm and a working pressure of 0.3 Torr. The sodium source, titanium source, aluminum source, phosphorus source, and oxygen source were pulsed in sequence, with purge times of 2s, 1.5s, 0.3s, 2s, and 20s, respectively. After each purge, high-purity nitrogen was used for 20s purging. This cycle was repeated 15 times, and the deposition thickness was 20nm, resulting in a sodium aluminum titanium phosphate fast ion conductor layer. The deposited electrode was transferred to a tube furnace, with argon as the protective atmosphere. The heating rate was 5℃ / min, and the temperature was raised to 550℃. The reaction was carried out for 2h to form the second coating. After cooling, the composite current collector was obtained.

[0070] The composite current collectors prepared in each embodiment and comparative example were assembled into coin cells with positive electrode sheets coated with sodium iron pyrophosphate. A 1M NaPF6 in EC:DEC=1:1 vol% electrolyte and a glass fiber separator were used. Assembly was conducted in a glove box (water and oxygen content <0.1 ppm). The assembled coin cells were then subjected to room temperature first-cycle discharge capacity testing, first coulombic efficiency testing, capacity retention testing after 300 cycles at room temperature, -20℃ low-temperature discharge performance testing, and composite current collector surface deposition morphology testing after the first charge cycle. The test methods are as follows, and the test results are shown in Table 1.

[0071] (1) First discharge capacity, first effect, and capacity retention rate after 300 cycles at room temperature. The assembled coin cells were charged to 3.8V at a constant current and constant voltage of 0.2C under room temperature (25℃) conditions, with a cutoff current of 0.05C. They were then discharged to 1.5V at a constant current of 0.2C, and the first discharge capacity and first efficiency were recorded. Cyclic testing was then performed under the same conditions, and the capacity retention rate after 300 cycles was recorded (based on the discharge capacity of the third cycle). (2) Discharge capacity retention test at -20℃ The lithium-ion battery was placed in an environment of 25°C and charged at a constant current of 0.2C to 3.8V, then charged at a constant voltage until the current dropped to 0.05C, and then discharged at a constant current of 0.2C to 1.5V. The discharge capacity at this point was recorded as C0. The battery was then charged at a constant current of 0.2C to 3.8V, then charged at a constant voltage until the current dropped to 0.05C, and then placed in an environment of -20°C and discharged at a constant current of 0.2C to 1.5V. The discharge capacity at this point was recorded as C1.

[0072] Low-temperature discharge capacity retention rate = C1 / C0 × 100% (3) Characterization of the sedimentary morphology of composite current collectors The coin cell battery from Example 1, after its first charge, was disassembled in a glove box. The composite current collector electrode was removed, and the surface residual electrolyte was cleaned with DEC solvent and dried. The deposition morphology of sodium metal on the surface of the composite current collector was observed using a scanning electron microscope. Figure 2 It can be seen that sodium is deposited densely and uniformly on the composite current collector of the present invention.

[0073] Table 1 Performance test results of the examples and comparative examples

[0074] As can be seen from the test results in Table 1, compared with Comparative Examples 1-3, the composite current collectors of Examples 1-5 of the present invention have superior overall electrochemical performance.

[0075] Specifically, as can be seen from Example 1 and Comparative Example 1, when the first coating does not contain sodium-loving metal quantum dots, it may be due to uneven deposition of metallic sodium, the presence of sodium dendrites and dead sodium, which leads to a significant decrease in overall first efficiency, cycle life and low-temperature performance. As can be seen from Example 1 and Comparative Example 2, when a fast ion conductor layer is not present, the structure of the first-cycle SEI film is unstable, consuming relatively more active sodium, resulting in a decrease in initial efficiency. Furthermore, the unstable SEI film is prone to rupture and side reactions during subsequent charge-discharge processes, continuously consuming active sodium, leading to a significant decrease in both room-temperature and low-temperature cycling performance. As shown in Examples 1 and 5 and Comparative Example 3, when the conductive carbon black is not subjected to acid treatment and nitrogen doping modification, the surface of the carbon material matrix is ​​flat and has few defects, making it difficult for metal quantum dots to grow and adhere in situ on its surface, and the overall conductivity of the untreated carbon material is worse. Therefore, the overall deposition effect of metallic sodium on the negative electrode side is poor, and the internal polarization of the battery is greater, resulting in a decrease in initial efficiency, cycle life, and low-temperature performance.

[0076] As shown in Examples 1 and 2, using sodium-affinity metal substrates can effectively improve the deposition effect of metallic sodium, and the cycling performance at room temperature and low temperature is similar, proving the universality of this method. The difference in performance mainly comes from the sodium deposition nucleation barrier, with zinc < tin.

[0077] As can be seen from Examples 1 and 4, when the amount of metal quantum dots attached in situ is large, it will affect the surface porous structure of the carbon material and the ability to mitigate volume expansion during the alloying process between sodium ions and metal quantum dots, thereby causing a decrease in the overall performance of the battery.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A composite current collector, characterized in that, include: Metal foil; A first coating is applied to the surface of the metal foil. The first coating includes an adhesive and modified conductive carbon black. The modified conductive carbon black is an inorganic element-doped porous conductive carbon black, and sodium-loving metal quantum dot particles are distributed in the channels of the modified conductive carbon black. The second coating is disposed on the surface of the first coating away from the metal foil, and the second coating is a fast ion conductor layer.

2. The composite current collector according to claim 1, characterized in that, The mass ratio of the adhesive, the modified conductive carbon black, and the sodium-loving metal quantum dot particles is 1:6~8:1~3.

3. The composite current collector according to claim 1, characterized in that, The thickness of the first coating is 1.5µm to 5µm, and the loading of the first coating is 0.3mg / cm³. 2 ~0.8mg / cm 2 The thickness of the second coating is 10nm~30nm.

4. The composite current collector according to claim 1, characterized in that, The substrate material of the modified conductive carbon black includes at least one of acetylene black, Ketjen black, and Super P; the sodium-loving metal quantum dot particles include at least one of gold quantum dot particles, silver quantum dot particles, indium quantum dot particles, zinc quantum dot particles, bismuth quantum dot particles, and tin quantum dot particles; the inorganic element is selected from at least one of nitrogen, sulfur, fluorine, and phosphorus; the material of the fast ion conductor layer is selected from at least one of sodium aluminum titanium phosphate, sodium titanium phosphate, sodium zirconium phosphate, sodium monofluorophosphate, and alumina.

5. The composite current collector according to claim 4, characterized in that, The substrate material of the modified conductive carbon black is selected from Ketjen black; the sodium-loving metal quantum dot particles are selected from zinc quantum dot particles; and the material of the fast ion conductor layer is selected from sodium aluminum titanium phosphate.

6. A method for preparing a composite current collector according to any one of claims 1 to 5, characterized in that, Including the following steps: (1) The conductive carbon black is first acid-treated and then inorganic element doping is performed to obtain modified conductive carbon black; (2) The sodium-loving metal source, surfactant and the modified conductive carbon black are mixed and reacted in a solvent composed of water, ethanol and ammonia to form hydroxide on the surface of the modified conductive carbon black. The hydroxide is then heat-treated in a reducing atmosphere to decompose the hydroxide and generate sodium-loving metal quantum dot particles to obtain modified conductive carbon black with sodium-loving metal quantum dot particles attached. (3) The modified conductive carbon black with attached sodium-loving metal quantum dot particles is mixed with a binder to form a slurry, which is then coated onto the surface of a metal foil to form a first coating. (4) A fast ion conductor layer is deposited on the surface of the first coating by atomic layer deposition technology, and a second coating is formed after heat treatment to obtain the composite current collector.

7. The method for preparing the composite current collector according to claim 6, characterized in that, In step (1), the acid treatment is carried out in a nitric acid solution with a concentration of 14 mol / L to 15 mol / L, a volume ratio of water to nitric acid of 15 to 5:1, a treatment temperature of 60℃ to 80℃, and a treatment time of 6h to 12h; the inorganic element doping is achieved by gas phase doping.

8. The method for preparing the composite current collector according to claim 6, characterized in that, In step (2), the mass ratio of the surfactant to the modified porous conductive carbon black is 0.05~0.1:1, the volume ratio of water, ethanol and ammonia is 8:1~3:0.5~2, the concentration of the sodium-loving metal source in the reaction solution is 0.1mol / L~2mol / L, the reducing atmosphere is a mixture of argon and hydrogen, the volume ratio of argon to hydrogen is 10:1~2, the temperature of the reduction heat treatment is 300℃~500℃, and the holding time is 1h~3h.

9. The method for preparing the composite current collector according to claim 6, characterized in that, In step (4), the reaction chamber temperature of the atomic layer deposition process is 150℃~200℃, the working pressure is 0.2Torr~0.5Torr, and the number of cycles is 10~20 times; the heat treatment includes treatment at 500℃~600℃ for 1~3 hours under a protective atmosphere.

10. A sodium metal battery without a negative electrode, characterized in that, The composite current collector includes the composite current collector as described in any one of claims 1 to 5 or the composite current collector prepared by the method described in any one of claims 6 to 9.